1999
DOI: 10.1037/h0087321
|View full text |Cite
|
Sign up to set email alerts
|

Context and homograph meaning resolution.

Abstract: We describe an activation-based model of word recognition and apply it to the process of resolving the meaning of homographs presented in context. The interpretation of homographs was assessed by asking participants to decide whether a target word was related to the meaning of a sentence containing a homograph. These relatedness decisions varied systematically with the relative frequency of the homograph meanings, delay, and the nature of the sentence context. In the model, it was assumed that orthographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Frequency or repetition effects on spontaneous cognition imply that cognitions relevant to risky behaviors arise because of many previous activations of those cognitions. This view is consistent with basic research on memory, in which frequency of activation has had important effects on later cognition (e.g., Dixon & Twilley, 1999), as well as research on social cognition (e.g., Bargh, Lombardi, & Higgins, 1988), which has suggested that chronically activated constructs are potent influences on behavior. Associative or relational effects imply that something in particular (e.g., setting, object, word, person, feeling) has become related enough through experience to subsequently act as a cue or trigger that spontaneously activates the cognition in memory (e.g., Nelson et al, 1998).…”
Section: Translation Of Specific Processes From Basic Research and Mesupporting
confidence: 88%
“…Frequency or repetition effects on spontaneous cognition imply that cognitions relevant to risky behaviors arise because of many previous activations of those cognitions. This view is consistent with basic research on memory, in which frequency of activation has had important effects on later cognition (e.g., Dixon & Twilley, 1999), as well as research on social cognition (e.g., Bargh, Lombardi, & Higgins, 1988), which has suggested that chronically activated constructs are potent influences on behavior. Associative or relational effects imply that something in particular (e.g., setting, object, word, person, feeling) has become related enough through experience to subsequently act as a cue or trigger that spontaneously activates the cognition in memory (e.g., Nelson et al, 1998).…”
Section: Translation Of Specific Processes From Basic Research and Mesupporting
confidence: 88%
“…That remindings can influence the interpretation of homographs provides a new perspective of the influence of reminding because, in the ordinary course of language comprehension, we are frequently unaware of a word’s multiple possible meanings (Dixon & Twilley, 1999; Yates, 1978). Resolving the lexical ambiguity of homographs may happen very quickly, and yet, remindings play a part in resolving the ambiguity of the homographs studied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dixon and Twilley (1999) proposed a model of meaning resolution with ambiguous words in which meaning activation was a logistic function of perceptual and contextual input. Consequently, in this theory, logistic regression provides a suitable, theoretically guided analysis of meaning selection data (e.g., Twilley & Dixon, 2000).…”
Section: Logistic Regression As An Alternativementioning
confidence: 99%